ID 274 – Separating idea from the action: A standardized low-resolution brain electromagnetic tomography (sLORETA) study. Issue 3 (March 2016) - Rakusa, M.; Busan, P.; Battaglini, P.P.; Zidar, J.
Abstract : Objective: We compared the temporal dynamics of sensory-motor network during the preparation of actual and imagined reaching and tried to separate ideational-to-motor from pure ideational part of motor program. Methods: Ten volunteers reached or imagined reaching with right arm. EEG and reaction time were recorded. Event related potentials were analysed with sLORETA (http://www.uzh.ch/keyinst/loreta ), comparing preparation of both tasks with respect to their baseline and between them. Results: Reaction time for actual reaching was 360 ± 59 ms. There were three key differences between tasks with stronger activity during actual reaching. The first was from 160 ms to 220 ms after target presentation in frontal and parietal regions, the second from 220 ms to 320 ms, in premotor cortex and the third from 320 ms to the reaching onset, mainly in the peri-rolandic region. These brain regions can be crucial for real reaching; processing arm-target integration and muscle activation. Anterior and posterior cingulate cortex were also involved most likely in awareness and controlling of the process. Conclusions and key message: Our results suggest the existence of two systems: cortical/integrational and subcortical/controlling system. Observed differences in the first system may be important in separating the ideational from the motor part of the program.